Pengaruh Kepercayaan, Fitur Layanan, Kenyamanan dan Kemudahan Penggunaan Terhadap Minat Konsumen Untuk Menggunakan Aplikasi Pemesanan Tiket Kapal Online - Rahmasari, Lisda; Dewa, Adenanthera Lesmana (Jurnal Ilmiah Aset, 2023)
The development of technology is very fast as it is supported by internet technology applications. On the other hand, the mobility of the individual is higher so they need application technologies that can respond to all the requests and needs of mobility. Within this condition it is very beneficial if then pemanfaatan all devices based on technology has become a way of life and like work because almost all jobs require high application of technology.In accordance with the development of technology that is implemented in transportation equipment that is not much found in sea vessels that can be accessed through mobile devices, well from the schedule of the ferry, information and for sending the ticket to a company. An android based mobile application can be planned which should solve those problems. This application is available to use the fast property of Android OS used for ordering ticket kapal laut, find out the schedule of kebarankatkan from different kapal due to payment. Application booking ticket online kapal laut based on android using the methodology DAD (Disciplined Agile Delivery) should provide information for communities where to travel with sea transportation, get information about kapal, sailing schedule, order tickets for each.